Three new genera and new species of hystrignathid nematodes (Nematoda: Thelastomatoidea) from passalid beetles (Insecta: Passalidae) from Yunnan Province, China with phylogenetic analysis of Hystrignathidae - Zhang, Ningning; Yin, Shi; Carreno, Ramon A.; Zhang, Luping (Zootaxa, 2021)
Three new genera and three new species of hystrignathid nematodes were collected from the hindgut of passalid beetles in the Yunnan Province, China. Huntia morffei gen. n. et sp. n. from Ceracupes fronticornis (Westwood) differs from related genera in the shape of the stoma, in the cephalic structure, and in the lack of annulation in the cervical region. Parakongonema sinica gen. n. et sp. n. from Aceraius grandis (Burmeister) and C. fronticornis can be easily distinguished from related genera in having the oral opening surrounded by a cuticular ring, the ring being surrounded by a cuticular flap, in the shape of the oesophagus, and in the cephalic structure. Parahystrignathus tongbiguanensis gen. n. et sp. n. from C. fronticornis and A. grandis differs from related genera by having the cervical region armed with alternating rows of spines, with 16 spines in the first row, and by lacking the first cephalic annule. In addition, the 18S and 28S rDNA partial sequences of three new species were obtained. The phylogeny of Hystrignathidae was inferred using partial sequences of the 28S rDNA and revealed patterns that suggest that the shape of the parasite digestive tract may reflect the evolutionary relationships of hystrignathid nematodes.